STRATEGI PENGEMBANGAN PARIWISATA MELALUI TRADISI BUDAYA TERHADAP PEREKONOMIAN MASYARAKAT DESA ADAT ASAK KARANGASEM - Ni Wayan Ari Sudiartini; Putu Ari Mulyani; Yenni Rahman (UNHI Press, 2020)
The purpose of this study is to understand the tourism development strategies in the Indigenous Village of Asak Karangasem, which analyzes the impact of tourism development through cultural traditions on the economy of the community and describes the tourism development strategies that will be carried out and can find out aspects that need to be considered in tourism development so that it can affect the economy of the village community. This study uses the SWOT analysis method where by using this analysis we can find out the strengths, weaknesses, opportunities and threats that exist around the Asak Karangasem Indigenous Village. From the results of this study it can be proven that the tourism development strategy is able to have an impact on the economy of the surrounding community.